1988
DOI: 10.1161/01.cir.78.4.941
|View full text |Cite
|
Sign up to set email alerts
|

Reversion of cardiac hypertrophy and reduced arterial compliance after converting enzyme inhibition in essential hypertension.

Abstract: Blood pressure, forearm arterial hemodynamics (with a pulsed Doppler flowmeter), and echocardiographic parameters were studied in 16 patients with sustained essential hypertension before and 3 months after administration of the converting enzyme inhibitor perindopril. In a single-blind study versus placebo, it was shown that perindopril significantly reduced blood pressure (p Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
8

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(91 citation statements)
references
References 49 publications
(19 reference statements)
4
79
0
8
Order By: Relevance
“…It is therefore difficult to compare the results with those of previous studies, which studied non-diabetic patients, 14,[28][29][30][31] used monotherapy 14,[32][33][34] or were short-term. 16 The design of this study was meant to reflect clinical practice, in which hypertensive type II diabetic patients typically need more than one agent to achieve adequate blood pressure regulation according to current guidelines. 35 In this context, we show that aggressive antihypertensive treatment decreases LVM index and arterial stiffness, which may thus be pathways through which such treatment reduces cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore difficult to compare the results with those of previous studies, which studied non-diabetic patients, 14,[28][29][30][31] used monotherapy 14,[32][33][34] or were short-term. 16 The design of this study was meant to reflect clinical practice, in which hypertensive type II diabetic patients typically need more than one agent to achieve adequate blood pressure regulation according to current guidelines. 35 In this context, we show that aggressive antihypertensive treatment decreases LVM index and arterial stiffness, which may thus be pathways through which such treatment reduces cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] In addition, it has been suggested that left ventricular hypertrophy and arterial stiffness are more effectively reduced by renin-angiotensin system inhibitors than by diuretics 14,15 because ACE inhibitors and AT1 receptor antagonists may reverse structural changes of myocardium and large arteries 16 by inhibition of myocardial and vascular growth factors. However, the effects of aggressive antihypertensive strategies on left ventricular hypertrophy and arterial stiffness in type II diabetes (which itself is a risk factor for these conditions) have not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical evaluation of vascular damage is performed through study of changes in: (1) intimal medial thickness (IMT) of carotid arteries during carotid duplex ultrasound examination; (2) vascular endothelial function and (3) arterial compliance. At equal degrees of reduction in blood pressure, RAS inhibitors produced a greater reduction in carotid IMT, 36,37 greater improvement in vascular endothelial function assessed non-invasively by flow mediated dilatation in brachial artery 18,38 and in arterial compliance 18,39 when compared with other antihypertensive agents.…”
Section: Benefits Of Ras Inhibitors Beyond Blood Pressure Loweringmentioning
confidence: 99%
“…[60][61][62] Accumulating evidence from recent clinical trials suggest beneficial effects of ACE inhibitors on arterial stiffness. [63][64][65][66][67] A small placebo-controlled trial showed that 3-months treatment with the ACE inhibitor perindopril increased brachial artery compliance and decreased pulse wave velocity. 63 These favourable effects on forearm arterial haemodynamics returned toward baseline values 4 weeks after treatment withdrawal.…”
Section: Effects Of Antihypertensive Drugs On Arterial Stiffnessmentioning
confidence: 99%
“…[63][64][65][66][67] A small placebo-controlled trial showed that 3-months treatment with the ACE inhibitor perindopril increased brachial artery compliance and decreased pulse wave velocity. 63 These favourable effects on forearm arterial haemodynamics returned toward baseline values 4 weeks after treatment withdrawal. 63 A large multicentre uncontrolled study in 1703 hypertensive subjects showed that the antihypertensive effect of perindopril administered for 6 months was accompanied by a significant decrease in carotid-femoral pulse wave velocity.…”
Section: Effects Of Antihypertensive Drugs On Arterial Stiffnessmentioning
confidence: 99%